A case of the orocraniodigital (Juberg-Hayward) syndrome. - Nevin, N C (1981)
A female with the orocraniodigital (Juberg-Hayward) syndrome is described in whom, in addition to bilateral cleft lip and palate, mild microcephaly, and anomalous thumbs and toes, there was absence of the pituitary fossa and a more widespread skeletal dysplasia.